Uma abordagem sobre energia solar por meio da aprendizagem baseada em projetos - Nascimento, Lucielen Nunes Barroso (2019)
The present work proposes the use of Project-Based Learning (PBL) as a strategy for teaching and learning concepts related to the use and application of solar energy, mainly covering photovoltaic solar energy for the generation of electricity, also addressing environmental issues of great importance for this issue. Thus, it was intended to collaborate for the training of the student of the electrician course in the modality of professional qualification with regard to the importance and applicability of this energy source, also contributing to achieve significant learning, theory to which this work is based. The research was based on the idea of action research in which participants are mobilized for the construction of knowledge in a process of reflection of the action, causing those involved to play an active role in solving problems, which were approached through an everyday question, from a perspective of the PBL. As an instrument for evaluation and data collection, a heading was used, in which it was possible to monitor the participants throughout the project developed, describing a possible learning result, a questionnaire was also applied to analyze the students' experience with regard to participation and involvement with PBL. At the end of the application, it was found that PBL is a strategy of relevant use in the classroom, since it contributed to learning becoming more dynamic and more autonomous studies. Regarding learning, it was possible to verify that the students were able to have a greater interactivity with the theme studied, demonstrating an understanding of various concepts, such as system types, equipment, operation, characteristics etc.